Evaluation of maternal serum folate, vitamin B12, and homocysteine levels andfactor V Leiden, factor II g.20210G>A, and MTHFR variations in prenatallydiagnosed neural tube defects - (:unkn) unknown (My University, 2016)
0

Background/aim: Neural tube defects (NTDs) are common congenital malformations that develop as a result of interactions between several genes and environmental factors. Many factors have been investigated in order to understand the etiology of NTDs, and many studies have identified folate intake as a common contributing factor. The exact etiology of the disease is still unknown. Materials and methods: In this study, we compared serum folate, vitamin B12, and homocysteine levels, along with common thrombophilia-related genetic variations, including factor V Leiden, factor II g.20210G>A, MTHFR c.677C>T, and MTHFR c.1298A>C, in 35 pregnant women with fetal NTDs and 38 pregnant women with healthy fetuses. Results: A significant difference in serum vitamin B12 level and factor V Leiden frequency was detected between the two groups. On the other hand, serum folate, homocysteine levels, and factor II g.20210G>A, MTHFR c.677C>T, and MTHFR c.1298A>C were not significantly different in the NTD group compared to the controls. Conclusion: These results indicate that vitamin B12 supplementation along with folate may help in lowering NTD frequency. In addition, this is the first study that provides evidence for a possible relationship between increased NTD risk and factor V Leiden.
Keywords: Cerrahi